Contrasting Responses in the Niches of Two Coral Reef Herbivores Along a Gradient of Habitat Disturbance in the Spermonde Archipelago, Indonesia - Plass-Johnson, Jeremiah G.; Bednarz, Vanessa N.; Hill, Jaclyn M.; Jompa, Jamaluddin; Ferse, Sebastian C. A.; Teichberg, Mirta (Frontiers in Marine Science, 2018)
Habitat modification of coral reefs is becoming increasingly common due to increases in coastal urban populations. Coral reef fish are highly dependent on benthic habitat; however, information on species-specific responses to habitat change, in particular with regard to trophic strategies, remains scarce. This study identifies variation in the trophic niches of two herbivorous coral reef fishes with contrasting trophic strategies, using Stable Isotopes Bayesian Ellipses in R, along a spatial gradient of changing coral reef habitats. In the parrotfish, Chlorurus bleekeri, a roving consumer, the range of 15N (positive) and 13C (negative) and their niche area (positive) displayed significant relationships with the amount of rubble in the habitat. In contrast, the farming damselfish, Dischistodus prosopotaenia, showed a narrow range of both 15N and 13C, displaying little change in niche parameters among sites. This may indicate that parrotfish vary their feeding according to habitat, while the damselfish continue to maintain their turf and invertebrate resources. Assessing isotopic niches may help to better understand the specific trophic responses to change in the environment. Furthermore, the use of isotopic niches underline the utility of stable isotopes in studying the potential impacts of environmental change on feeding ecology.